How live stream content types impact viewers’ support behaviors? Mediational analysis on psychological and social gratifications - Mao, Eric (Frontiers in Psychology, 2022)
While previous research into live streaming was predominantly focused on video games, its content creation and provision has tremendously evolved, extending well beyond game streams. Contents of general interest, such as e-commerce shopping, talent shows, and cute pets, started to prevail in today’s landscape of live streaming. However, limited attention has been given to how distinct types of streaming contents influence viewers’ psychological and behavioral responses. To fill this void, we employed an online survey (n = 583) to empirically examine the associations between popular live stream content types on Douyin (i.e., the TikTok app for China) and their viewers’ psychological and social gratifications and typical support behaviors. The results revealed that gratifications varied drastically across different content types. Game streaming, in particular, generated significant indirect impacts on all the support behaviors under consideration. On the other hand, whereas tension release served as a consistent mediator, the cognitive needs had no significant mediation effects. In sum, our study makes theoretical contributions to the literature by analyzing the thriving live stream phenomenon from a use and gratification perspective. We help augment the understanding of new media users’ preferences and choices in an attention economy, wherein human attention is conceptualized as a scarce resource. In practice, a better knowledge of viewer needs can facilitate streamers to customize their content creation and provision so as to accentuate elements of interest and elicit desired support behaviors (i.e., monetization opportunities).